SUPEROVULATORY RESPONSE AND EMBRYO RECOVERY IN SURTI BUFFALOES USING FSH AND DIFFERENT DOSES OF PMSG - SAREN, A K; SHAH, R G (The Indian Journal of Animal Reproduction, 2010)
The experiment was conducted to study superovulatory response and embryo recovery rate in18 Surti buffaloes of 2-6 parity during breeding season (August to February) using FSH and two dosesof PMSG. Animals were divided into three groups. Group I (n=6) and Group II (n=6) donors weresuperovulated with single i/m dose of 2500 and 3000 I U PMSG, respectively, on day 10 of the estrouscycle, whereas Group Ill (n=6) donors were treated intramuscularly with 400 mg FSH per donor in 8equal doses 12 hrs apart. Luteolysis was carried out on day 12 using PGF2«. A!l the animals were bredat _superovulatory estrus. Almost all the animals responded to superovulation. Flushing was performedon day 6 after superestrus. The mean number of ovulations and embryo recovery rates in three groups(I, II and Ill) were2.67, 3.50, 4.67 and 0.00, 0.17, 0.17, respectively. The mean numbers of unovulatedfollicles were 1.67, 2.17 and 1.00, respectively, in the three groups.
Keywords: Buffalo; Superovlation; FSH; PMSG